2018
DOI: 10.3389/fncel.2018.00479
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes Observed in the Piriform Cortex in a Rat Model of Pre-motor Parkinson’s Disease

Abstract: Early diagnosis of Parkinson’s disease (PD) offers perhaps, the most promising route to a successful clinical intervention, and the use of an animal model exhibiting symptoms comparable to those observed in PD patients in the early stage of the disease, may facilitate screening of novel therapies for delaying the onset of more debilitating motor and behavioral abnormalities. In this study, a rat model of pre-motor PD was used to study the etiology of hyposmia, a non-motor symptom linked to the early stage of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 158 publications
0
22
0
Order By: Relevance
“…Deimination has hitherto not been assessed in pre-motor PD and was therefore the subject of our current study as such post-translationally mediated changes may result in early onset pro-inflammatory and neurodegenerative processes and therefore offer an opportunity for early intervention. Interestingly, in the current study using a rat model of pre-motor PD, that has been shown to display non motor symptoms in the absence of motor dysfunction and neuroinflammation [32], an increase in deiminated proteins was observed in the brain vasculature, particularly in the cortex and hippocampus. Such elevated F95 positive detection observed here correlates somewhat with a previous study on human PD post-mortem brain tissue, although that study reported elevation of deiminated proteins in the substantia nigra [10].…”
Section: Discussionmentioning
confidence: 43%
See 4 more Smart Citations
“…Deimination has hitherto not been assessed in pre-motor PD and was therefore the subject of our current study as such post-translationally mediated changes may result in early onset pro-inflammatory and neurodegenerative processes and therefore offer an opportunity for early intervention. Interestingly, in the current study using a rat model of pre-motor PD, that has been shown to display non motor symptoms in the absence of motor dysfunction and neuroinflammation [32], an increase in deiminated proteins was observed in the brain vasculature, particularly in the cortex and hippocampus. Such elevated F95 positive detection observed here correlates somewhat with a previous study on human PD post-mortem brain tissue, although that study reported elevation of deiminated proteins in the substantia nigra [10].…”
Section: Discussionmentioning
confidence: 43%
“…Rats were divided into two experimental groups: sham-treated animals (n = 3) and toxin-treated model (pre-motor model-n = 3). This pre-motor PD model was shown to present non-motor symptoms in the absence of motor dysfunction in a previous study [32]. The pre-motor PD models did not present any motor dysfunction prior to culling.…”
Section: Induction Of the Rat Model Of Pre-motor Pdmentioning
confidence: 54%
See 3 more Smart Citations